Survey on brachytherapy training among radiation oncology residents in the German-speaking regions of Europe - Knoth, Johannes; Konrad, Stefan; Lössl, Kristina; Motisi, Laura; Mäurer, Matthias; Linde, Philipp; Lindel, Katja; Niehoff, Peter; Strnad, Vratislav; Sturdza, Alina; Corradini, Stefanie (Strahlentherapie und Onkologie, 2023)
Purpose: This survey aimed to determine the perception of brachytherapy training among residents in the DACH region, consisting of Austria, Germany and Switzerland. Material & Methods: An online questionnaire containing 22 questions related to trainee demographics (n = 5) and to brachytherapy training (n = 17) was sent in two iterations in 11/2019 and 02/2020. The following topics were evaluated: institutional support, barriers to training, extent of training, site-specific training (prostate, gynaecology, breast, gastrointestinal and skin), preferences for further training and outlook on overall development of brachytherapy. The responses were mostly based on a Likert scale of 1 to 5, thereby reflecting strength of opinion. Descriptive statistics were used to describe frequencies. Results: Among the 108 respondents, approximately 69% of residents considered the ability to perform brachytherapy independently to be important or somewhat important. However, only 31% of respondents reported to have a dedicated brachytherapy training during residency. The major limitation to achieve independence in performing brachytherapy was seen in a low case load in Austria, in the lack of training in Switzerland and in both of them in Germany. Conclusion: The interest in brachytherapy training among residents in German-speaking countries was generally high, but there is a perceived lack of sufficient case volumes and partially also in formal training opportunities. Fellowships at departments with a high case load as part of a formalised curriculum and dedicated hands-on workshops at national or international conferences might help to overcome these issues.
CRIS-Team Scopus Importer:2023-07-28
Keywords: Career choice; Education; Questionnaire; Survey; Teaching